Asumsi Dasar Ilmu Pengetahuan - Anton Ismunanto (Tasfiyah: Jurnal Pemikiran Islam, 2017)
Every man understand that knowledge is important for their life, on the contrary, they understand that ignorance may have some bad impacts for their life. Yet, most people don’t really understand about what they mean by knowledge. This paper tries to explain about that. Firstly, this paper tries to make clear about the terms that’s being used in daily life that have correlation with knowledge. Then, this paper will give the details of the assumptions that correspond with knowledge. Starting with the ontogical assumption that will make clear about the nature of knowledge. It is including non-positive or non-empirical knowledge that possible to be obtained by man. Then, come to the epistemological assumption that explains about the types of inquiry knowledge. It is because the differentiations of each knowledges have their own consequence toward the different ways to inquiry it. Lastly, it will be clear that the axiological assumption talking about the influence of knowledges to the human life, will be including the ethics that have to be owned by every knowledgable person (every man whose knowledges are existed in their selfs). So, it will be clear for every reader about what they really mean with the word ‘knowledge’ in their daily words.